Role of microRNAs in trophoblast invasion and spiral artery remodeling: Implications for preeclampsia - Hayder, Heyam; Shan, Yanan; Chen, Yan; O’Brien, Jacob Anderson; Peng, Chun (Frontiers in Cell and Developmental Biology, 2022)
It is now well-established that microRNAs (miRNAs) are important regulators of gene expression. The role of miRNAs in placental development and trophoblast function is constantly expanding. Trophoblast invasion and their ability to remodel uterine spiral arteries are essential for proper placental development and successful pregnancy outcome. Many miRNAs are reported to be dysregulated in pregnancy complications, especially preeclampsia and they exert various regulatory effects on trophoblasts. In this review, we provide a brief overview of miRNA biogenesis and their mechanism of action, as well as of trophoblasts invasion and spiral artery remodeling. We then discuss the role miRNAs in trophoblasts invasion and spiral artery remodeling, focusing on miRNAs that have been thoroughly investigated, especially using multiple model systems, and their potential role in the pathogenesis of preeclampsia.